Asymmetrical β-actin mRNA translation in growth cones mediates attractive turning to netrin-1 - Leung, Kin-Mei (2006)
Local protein synthesis regulates the turning of growth cones to guidance cues yet little is known about which proteins are synthesized or how they contribute to directional steering. Here we show that β-actin mRNA resides in Xenopus retinal growth cones where it binds to the RNA-binding protein, Vg1RBP. Netrin-1 induces the movement of Vg1RBP granules into filopodia suggesting that it may direct the localization and translation of mRNAs in growth cones. Indeed, a gradient of netrin-1 activates the translation initiation regulator, eIF4E-BP, asymmetrically and triggers a polarized increase in β-actin translation on the near side of the growth cone prior to growth cone turning. Inhibition of β-actin translation abolishes both the asymmetric rise in β-actin and attractive, but not repulsive, turning. Our data suggest that newly synthesized β-actin, concentrated near sites of signal reception, provides the directional bias for polymerizing actin in the direction of an attractive stimulus.